PENINGKATAN HASIL BELAJAR AKIDAH AKHLAK DENGAN PEMANFAATAN APLIKASI QUIZIZZ PADA SISWA KELAS X DI MA MA’ARIF DURENSEWU - Aprillia, Sofia Sasa Bella; Saifulah, Saifulah; Kirom, Askhabul; Marzuki, Ahmad (Yayasan Rahmat Islamiyah, 2024)
The low learning outcomes of students' moral creed subjects in the learning process can be caused by the lack of use of learning media that suits the needs of students. This study aims to improve students' learning outcomes in moral creed through the use of the quizizz application. This type of research falls into the category of classroom action research, which was carried out in two research cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. The data source of this research is all X grade students of MA Ma'arif Durensewu, totaling 16 students in the academic year 2023/2024 Semester 2. Data collection in the study was carried out using questionnaires, learning percentage assessments, observation sheets, and documentation with research instruments in the form of learning outcomes test akidah akhlak. The data obtained in this study were then analyzed using qualitative and quantitative descriptive analysis techniques. The indicator of success is determined by the criterion that 90% of students achieve learning outcomes that meet the KKM of ?75. The results of this study indicate that the percentage of students who completed the KKM in cycle I was 25% to 100% in cycle II. Thus, it can be concluded that there is an increase in learning outcomes after using the quizizz application.